2013
DOI: 10.1371/journal.pone.0056440
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Heme Oxygenase-1 Gene Promoter Polymorphism and the Outcomes of Catheter Ablation of Atrial Fibrillation

Abstract: A length polymorphism of GT repeats in the promoter region of the human heme oxygenase-1 (HO-1) gene modulates its gene transcription to protect against myocardial injury. The present study investigated the association between HO-1 promoter polymorphisms and the outcomes of catheter ablation of atrial fibrillation (AF). The allelic frequencies of GT repeats in the HO-1 gene promoter were screened in 205 random individuals who underwent catheter ablation for drug refractory AF.In the patients who received cathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Over the last few years, several common genetic variants have been demonstrated to be associated with AF in GWAS performed in European ancestry [14] and the Chinese Han GeneID cohort [13]. Some reports have suggested that these genetic polymorphisms are associated with an increased risk of AF recurrence after RFCA [6][7][8][9]24]. However, there are ethnic differences in the frequency of these SNPs and their association with clinical phenotypes [10,13].…”
Section: Genetic and Patient Factors And Ablation Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Over the last few years, several common genetic variants have been demonstrated to be associated with AF in GWAS performed in European ancestry [14] and the Chinese Han GeneID cohort [13]. Some reports have suggested that these genetic polymorphisms are associated with an increased risk of AF recurrence after RFCA [6][7][8][9]24]. However, there are ethnic differences in the frequency of these SNPs and their association with clinical phenotypes [10,13].…”
Section: Genetic and Patient Factors And Ablation Outcomementioning
confidence: 99%
“…Therefore, we sought to identify patient factors predicting favorable success rates, and hypothesized that better patient selection criteria may improve clinical outcomes, reduce unnecessary cardiac tissue damage, or avoid unnecessary ablation procedures and reduce medical costs and procedure-related complications. Recently, there were several reports for the relationship between genetic polymorphism and clinical outcome of AF ablation [6][7][8][9]. Although there are significant ethnic differences [10], genetic polymorphism can be utilized as an innate biomarker to identify good responders for AF catheter ablation.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 However, there is only limited data correlating genotypes with outcomes of AF therapies [8][9][10] and in particular with rhythm outcome after AF ablation. [11][12][13] Consequently, this study tested the hypothesis that the angiotensin-converting enzyme gene (ACE) insertion/deletion polymorphism associates with AF recurrence after catheter ablation. Using a candidate gene approach, this polymorphism was selected because the ACE deletion allele, ACE D, is associated with increased ACE serum levels, higher cardiac ACE activity, and increased cardiac fibrosis.…”
Section: Clinical Perspective On P 737mentioning
confidence: 99%
“…It has also been previously shown that some genetic factors predict the risk of AF recurrence after catheter ablation181920212223. Recently, Husser et al 18.…”
Section: Discussionmentioning
confidence: 96%